Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3390/molecules18078417
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Water Extractable Arabinoxylans from a Spring Wheat Flour: Rheological Properties and Microstructure

Abstract: In the present study water extractable arabinoxylans (WEAX) from a Mexican spring wheat flour (cv. Tacupeto F2001) were isolated, characterized and gelled and the gel rheological properties and microstructure were investigated. These WEAX presented an arabinose to xylose ratio of 0.66, a ferulic acid and diferulic acid content of 0.526 and 0.036 µg/mg WEAX, respectively and a Fourier Transform Infra-Red (FT-IR) spectrum typical of arabinoxylans. The intrinsic viscosity and viscosimetric molecular weight values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
39
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 26 publications
17
39
2
Order By: Relevance
“…Nevertheless, the AX yields found in the present study were smaller than those previously reported [21], which could be related to the maize varieties used in each investigation. The yield found in this study is similar to reported by other sources of AX as wheat flour (0.5 %) [16]. In spite of low yield values, recuperation of AX from wastewater could be an advantage for future industrial applications of this polysaccharide.…”
Section: Extraction and Characterization Of Ax1 And Ax2supporting
confidence: 88%
See 4 more Smart Citations
“…Nevertheless, the AX yields found in the present study were smaller than those previously reported [21], which could be related to the maize varieties used in each investigation. The yield found in this study is similar to reported by other sources of AX as wheat flour (0.5 %) [16]. In spite of low yield values, recuperation of AX from wastewater could be an advantage for future industrial applications of this polysaccharide.…”
Section: Extraction and Characterization Of Ax1 And Ax2supporting
confidence: 88%
“…Phenolic compounds and proteins have specific absorption bands in the 1500 -1,700 cm -1 [23]. The region from 3500-1800 cm -1 is the fingerprint region of polysaccharides, with two bands (3,400 cm -1 corresponding to stretching of the OH groups and 2,900 cm -1 corresponding to the CH 2 groups) [16,25]. These results suggest that nixtamalization conditions used in the present study do not affect the structural features of AX.…”
Section: Extraction and Characterization Of Ax1 And Ax2mentioning
confidence: 46%
See 3 more Smart Citations